An Extremely Rare Case of Birk-Barel Syndrome With Severe Central Apneas - Ramirez-Arenalde, Michael A (Cureus, 2021)
Birk-Barel syndrome, alternatively known as KCNK9 imprinting syndrome, is caused by a missense mutation in the potassium two pore domain channel subfamily K member 9 (KCNK9) gene on chromosome 8q24.3. This syndrome demonstrates dominant inheritance and is imprinted with paternal silencing, where the paternally inherited allele is silenced, and the maternally inherited allele is active. Congenital hypotonia, palatal abnormalities, intellectual disability, severe feeding difficulties, and dysmorphic facial features characterize this sporadic genetic syndrome. To date, there are approximately 21 molecularly diagnosed individuals worldwide described in the literature. We describe the first known case of Puerto Rican ethnicity, a 16-month-old female born prematurely at 36-weeks with Birk-Barel syndrome, confirmed with whole-exome sequencing, and her response to non-invasive ventilation as a treatment for her sleep breathing disorder.